Early outcomes of a modern cemented total knee arthroplasty: is tibial loosening a concern?. (1st June 2021) - Yang, JaeWon; Heckmann, Nathanael D.; Nahhas, Cindy R.; Salzano, Michael B.; Ruzich, Gregory P.; Jacobs, Joshua J.; Paprosky, Wayne G.; Rosenberg, Aaron G.; Nam, Denis
Abstract : Aims: Recent total knee arthroplasty (TKA) designs have featured more anatomical morphologies and shorter tibial keels. However, several reports have raised concerns about the impact of these modifications on implant longevity. The aim of this study was to report the early performance of a modern, cemented TKA design. Methods: All patients who received a primary, cemented TKA between 2012 and 2017 with a minimum two-year follow-up were included. The implant investigated features an asymmetrical tibial baseplate and shortened keel. Patient demographic details, Knee Society Scores (KSS), component alignment, and the presence of radiolucent lines at final follow-up were recorded. Kaplan-Meier analyses were performed to estimate survivorship. Results: A total of 720 of 754 primary TKAs (95.5%) were included with a mean follow-up of 3.9 years (SD 1.3); 562 (78.1%) were cruciate-retaining and 158 (21.9%) were posterior-stabilized. A total of 11 (1.5%) required reoperation for periprosthetic joint infection and seven (1.0%) for aseptic tibial loosening (five cruciate-retaining, two posterior-stabilized). Loosening occurred at a mean of 3.3 years (0.9 to 6.5). There were no cases of loosening in the 33 patients who received a 14 mm × 30 mm tibial stem extension. All-cause survivorship was 96.6% at three years (95% confidence interval (CI) 95.3% to 98.0%) and 96.2% at five years (95% CI 94.8% to 97.7%). Survivorship with revision for aseptic loosening was 99.6% at three years (95% CI 99.1% to 100.0%) and 99.1% at five years (95% CI 98.4% to 99.9%). Tibial components were in significantly more varus in those with aseptic loosening (mean 3.4° (SD 3.7°) vs 1.3° (SD 2.0°); p = 0.015). There were no other differences in demographic, radiological, or surgical characteristics between revised and non-revised TKAs for aseptic loosening (p = 0.293 to 1.00). Mean KSS improved significantly from 57.3 (SD 9.5) preoperatively to 92.6 (SD 8.9) at the final follow-up (p < 0.001). Conclusion: This is the largest series to date of this design of implant. At short-term follow-up, the rate of aseptic tibial loosening is not overly concerning. Further observation is required to determine if there will be an abnormal rate of loosening at mid- to long-term follow-up. Cite this article: Bone Joint J  2021;103-B(6 Supple A):51–58.